A study of the effects of the pineal hormone, melatonin, on dopaminergic transmission in the central nervous system of rats - Burton, Susan Frances (Rhodes University, Faculty of Pharmacy, Pharmacy, 1990)
Dopamine mechanisms in the central nervous system are important in the control of both normal and abnormal motor function. The recent observations in both animal and human studies, that melatonin, the principal hormone of the pineal gland, may have a role in the control of movement and the pathophysiology of movement disorders, have given rise to the concept that melatonin may have a modulatory influence on central dopaminergic neurotransmission. This study makes use of three animal behavioural models as well as a biochemical model of central dopaminergic function to further investigate the concept. Results from studies using the biochemical model, which investigated the effect of melatonin on dopamine and apomorphine stimulation of dopamine-sensitive adenylate cylase, suggest that melatonin is neither a competitive antagonist nor agonist at the Dâ‚ receptor level, although the possibility of physiological stimulation or antagonism is not excluded. In behavioural studies, prior melatonin mg/kg administration (1 and 10 (8M) ip) inhibited apomorphine induced stereotypy and locomotor activity in normal rats, and apomorphine-induced rotational behaviour in 6-hydroxydopamine and quinolinic acid lesioned rats. The possibility that these results may have physiological significance is borne out by the observation that, under enviromental lighting conditions that are associated with raised endogeous melatonin levels, apomorphine- induced stereotypy and locomotor activity is attenuated. The general conclusion is that melatonin has an inhibitory influence on central nervous system dopaminergic function, suggesting therefore, that the pineal gland and melatonin may have a role in the pathophysiology and treatment of movement and behavioural disorders associated with dopaminergic dysfunction
Keywords: Dopaminergic mechanisms; Melatonin; Pineal gland -- Secretions; Neural transmission; Pineal gland; Nervous system